Assessment of anxiety and depression in patients with Posner-Schlossman syndrome - Chaoxu Qian; Zhi Da Soh; Sahil Thakur; Wen Yan; Xian Shao; Hua Zhong; Kaidi Wang (BMC Ophthalmology, 2023)
Abstract Background To assess the anxiety and depression levels in patients with Posner-Schlossman syndrome (PSS) and to determine the potential risk factors. Methods In this cross-sectional study, a total of 195 participants, including 93 PSS patients and 102 healthy controls were recruited. Sociodemographic and clinical information were collected for all participants. Hospital Anxiety and Depression scale (HADS) was administered to evaluate the anxiety and depression levels. Visual function (VF) and quality-of-life (QOL) questionnaires were administered to assess variables potentially associated with anxiety and depression. Results Increased anxiety level was observed in 22 (23.7%) PSS patients as compared to 10 (9.8%) of controls (P = 0.009). While the frequency of depression between the two groups was not significantly different (P = 0.349). The mean anxiety and depression scores were 6.98 ± 4.20 and 6.44 ± 3.66 in PSS patients as compared to 6.67 ± 3.21 (P = 0.564) and 5.96 ± 2.93 (P = 0.311) in controls. Logistic regression analysis showed mental well-being was significantly associated with anxiety (odds ratio [OR] = 0.920, 95% confidence interval [CI] = 0.881–0.962, P < 0.001) and depression (OR = 0.959, CI = 0.926–0.994, P = 0.023) in PSS patients. Conclusion More patients with PSS may experience anxiety as compared to healthy controls. Mental well-being is an independent risk factor for anxiety and depression. It is important for ophthalmologists to be aware of these factors and should pay more attention on mental health when PSS is managed in clinic.